Government policy for the internet must be rights-based and user-centered - Wafa Ben-Hassine (UN Chronicle, 2019)
Today there may be no resource as powerful, or as vulnerable, as data. The central role that data sharing plays in contemporary society, ranging from use of social media to accessing administrative services, is accompanied by a high degree of risk. Data sharing on a mass scale and for many purposes in a digitally connected world means that our personal information is increasingly open to attack and misuse. In our online communications and transactions, we risk exposing details about our lives that used to be private as a matter of course. This includes not just financial data that must be kept secure but also information about our location, our friends, families and associates, our political beliefs, our purchases and even our health data. Further, States across the globe are creating digital identity systems that connect to our biometric information, building a bridge from our digital activities to our lives and identity offline. This digital identity may then become the target of exploitation, either for commercial or political ends.